2023
DOI: 10.1101/2023.11.11.566336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modifications in the T arm of tRNA globally determine tRNA maturation, function and cellular fitness

Sarah K. Schultz,
Christopher D. Katanski,
Mateusz Halucha
et al.

Abstract: All elongator tRNAs harbor 5-methyluridine 54 and pseudouridine 55 in the T arm, which are generated by the enzymes TrmA and TruB, respectively.Escherichia coliTrmA and TruB both act as tRNA chaperones, and strains lackingtrmAortruBare outcompeted by wildtype. Here, we investigate how TrmA and TruB contribute to cellular fitness. Deletion oftrmAandtruBinE. colicauses a global decrease in aminoacylation and alters other tRNA modification such as acp3U47. Whereas overall protein synthesis is not affected in Δtrm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“… Modification circuits involving tRNA core modifications: ( a ) modification circuits identified in T. thermophilus in response to temperature changes represented on a cloverleaf scheme [ 94 , 95 , 107 ]; ( b ) T-arm modification circuits identified in yeast [ 69 , 70 ]; ( c , d ) modification circuits identified in E. coli [ 109 , 110 , 111 ]; and ( e ) modification circuits identified in E. coli [ 111 ]. Modifications are represented by colored circles (see the legend in the box for the corresponding colors).…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
See 4 more Smart Citations
“… Modification circuits involving tRNA core modifications: ( a ) modification circuits identified in T. thermophilus in response to temperature changes represented on a cloverleaf scheme [ 94 , 95 , 107 ]; ( b ) T-arm modification circuits identified in yeast [ 69 , 70 ]; ( c , d ) modification circuits identified in E. coli [ 109 , 110 , 111 ]; and ( e ) modification circuits identified in E. coli [ 111 ]. Modifications are represented by colored circles (see the legend in the box for the corresponding colors).…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
“…Recently, several reports have shed light on modification cross-talks among tRNA core modifications in E. coli . They reported that the introduction of U47 is globally enhanced by the prior presence of m 7 G46 [ 109 ] and also stimulated by m 5 U54 in E. coli , , , and [ 110 , 111 ] ( Figure 3 c). 55 seems to also participate in this network, in which it may either slightly stimulate or inhibit the introduction of U47 in E. coli and , respectively [ 111 ].…”
Section: Influence Of Trna Core Modification On Trna Structure and St...mentioning
confidence: 99%
See 3 more Smart Citations